Odpowiedź:
Szczegółowe wyjaśnienie:
zad. 1
S = [tex]x^{3}[/tex] - 2[tex]x^{2}[/tex] + 3[tex]x^{5}[/tex] - 4 = 3[tex]x^{5}[/tex] + [tex]x^{3}[/tex] - 2[tex]x^{2}[/tex] - 4
T = 3[tex]x^{2}[/tex] - 2[tex]x^{4}[/tex] + 4 - [tex]x^{3}[/tex] = -2[tex]x^{4}[/tex] - [tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] + 4
S + T = 3[tex]x^{5}[/tex] -2[tex]x^{4}[/tex] + [tex]x^{2}[/tex]
S - T = 3[tex]x^{5}[/tex] + [tex]x^{3}[/tex] - 2[tex]x^{2}[/tex] - 4 - (-2[tex]x^{4}[/tex] - [tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] + 4) = 3[tex]x^{5}[/tex] + 2[tex]x^{4}[/tex] + 2[tex]x^{3}[/tex] - 5[tex]x^{2}[/tex] - 8
zad. 2
x(x - 1) + 4(x - 2)(x + 1) = [tex]x^{2}[/tex] - x + 4([tex]x^{2}[/tex] + x - 2x - 2) = [tex]x^{2}[/tex] - x + 4[tex]x^{2}[/tex] + 4x - 8x - 8 = 5[tex]x^{2}[/tex] - 5x - 8
zad. 3
[tex]S^{2}[/tex] = [tex](x^{2} -4)^{2}[/tex] = [tex]x^{4}[/tex] - 8[tex]x^{2}[/tex] + 16
[tex]T^{2}[/tex] = [tex](x^{2} +4)^{2}[/tex] = [tex]x^{4}[/tex] + 8[tex]x^{2}[/tex] + 16